Natural Products with Potential in Parkinson’s Disease - Singh, Inder Pal; Singh, Virinder; Saini, Muskan (Indian Forester, 2022)
Parkinson’s disease (PD) is a neurodegenerative disease affecting people of older age group. The complete etiology of Parkinson’s disease is not known yet but there are some age related factors that contribute to this disease. Pathophysiology of PD includes various mechanisms like depletion of dopamine, oxidative stress by various reactive oxygen species (ROS), apoptosis of dopaminergic neurons, formation of Lewy bodies, aggregation of a-synuclein protein, genetic susceptibility and many others that still require further investigation. There are many herbs which have antioxidant potential and have been used since ancient times to treat various neurodegenerative disorders like Alzheimer, Epilepsy, Huntington’s as well as Parkinson’s disease. Many experimental studies have been conducted to determine the neuroprotective effect of herbal extracts against PD and to elucidate their mechanism of protection, however, further studies are still required to determine the active principles in many of these herbs producing this neuroprotective effect. In this review, Authors have identified and compiled herbal drugs active principles targeting PD.